2020
DOI: 10.3390/ijms21030877
|View full text |Cite
|
Sign up to set email alerts
|

miR-20b and miR-451a Are Involved in Gastric Carcinogenesis through the PI3K/AKT/mTOR Signaling Pathway: Data from Gastric Cancer Patients, Cell Lines and Ins-Gas Mouse Model

Abstract: Gastric cancer (GC) is one of the most common and lethal gastrointestinal malignancies worldwide. Many studies have shown that development of GC and other malignancies is mainly driven by alterations of cellular signaling pathways. MicroRNAs (miRNAs) are small noncoding molecules that function as tumor-suppressors or oncogenes, playing an essential role in a variety of fundamental biological processes. In order to understand the functional relevance of miRNA dysregulation, studies analyzing their target genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a class of small (22 nucleotides long), highly stable non-coding RNAs involved in post-transcriptional regulation of gene expression [ 7 ]. Deregulated miRNA expression profiles have been observed in virtually all major types of cancer, where they can act both as oncogenes or tumor suppressors and are associated with tumorigenesis, tumor progression, metastasis and drug resistance pathways [ 7 , 8 , 9 , 10 ]. Furthermore, miRNAs have been shown to exhibit a diagnostic or prognostic value and even have potential clinical implications for targeted gene therapy in cancer patients [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small (22 nucleotides long), highly stable non-coding RNAs involved in post-transcriptional regulation of gene expression [ 7 ]. Deregulated miRNA expression profiles have been observed in virtually all major types of cancer, where they can act both as oncogenes or tumor suppressors and are associated with tumorigenesis, tumor progression, metastasis and drug resistance pathways [ 7 , 8 , 9 , 10 ]. Furthermore, miRNAs have been shown to exhibit a diagnostic or prognostic value and even have potential clinical implications for targeted gene therapy in cancer patients [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies revealed that miRNA-20b expression was enhanced in GC tissue and was positively associated with lymph node metastasis [3]. Further, high level of miRNA-20b predicts poor survival for GC patients [24] and suppression of miRNA-20b displays an anti-tumor effect in vitro [25], suggesting the therapeutic potential of targeting miRNA-20b in GC. However, the oncogenic molecular mechanism of miRNA-20b is not well studied.…”
Section: Discussionmentioning
confidence: 92%
“…However, the role of miR-20b-5p in the pathogenesis of cancers is controversial. MiR-20b-5p has a tumor suppressive role in gastric cancer(GC) through regulation of the PI3K / AKT / mTOR signaling pathway [36] . Also, miR-20b-5p suppressed TGF-β1-induced migration and invasion of prostate cancer by up-regulating E-cadherin and down-regulating vimentin, leading to TGF-β1-induced inhibition of epithelial-to-mesenchymal transition (EMT) [31] .…”
Section: Discussionmentioning
confidence: 99%